If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 329 = 7(7x + -16) Reorder the terms: 329 = 7(-16 + 7x) 329 = (-16 * 7 + 7x * 7) 329 = (-112 + 49x) Solving 329 = -112 + 49x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49x' to each side of the equation. 329 + -49x = -112 + 49x + -49x Combine like terms: 49x + -49x = 0 329 + -49x = -112 + 0 329 + -49x = -112 Add '-329' to each side of the equation. 329 + -329 + -49x = -112 + -329 Combine like terms: 329 + -329 = 0 0 + -49x = -112 + -329 -49x = -112 + -329 Combine like terms: -112 + -329 = -441 -49x = -441 Divide each side by '-49'. x = 9 Simplifying x = 9
| X^2+15x+44=(x+4)(x+0) | | 5v^2-22v=0 | | 4(2v+1)-2(3v+5)=4(v-3)+w | | -5(-9x-15)=435 | | 4=8-2(2x-6) | | s^2-45s=0 | | -20=z^2-4x-12 | | 6x^3y^2-24x^3y^3= | | u^2+33u=0 | | 28=y-4+3y | | x^2+3x+40= | | 6x^3y^2-24x^3y^3=0 | | 6(7x+2)=474 | | 4(x+6)-9= | | 46h^2-9h=0 | | 7m-4=3m+20 | | d^2-34d=0 | | Xy-7x+5y-35=0 | | 6x+2+15=53 | | -120+8x-6=90 | | 41f^2-43f=0 | | 2y+7=5y-4 | | 6.21y+3-4.5y+1.45=-3.5y+6.2-2.8+y | | 10(2+x+3)= | | x^2-4x-12=-16 | | 2(4t-6)=24t+7 | | -12x+6x-48=30 | | -13(n+20)=-11(n+38) | | D(d+3)-d(d-4)=9d-6 | | m(3m+7)=-4 | | 276=-6(-9x+8) | | -5y(2y-3)=4(1-3y)+12 |